BEAUTY SALON BUSINESS DEVELOPMENT THROUGH INNOVATION AND DIGITAL MARKETING TO INCREASE FAMILY INCOME AT SALON MITRA LOMBOK TIMUR - Sulaimiah; Sulhaini; Harmi Widiana; Bq. Ismiwati (CV. Naskah Aceh, 2026)
Small and Medium Enterprises (SMEs) play an important role in supporting community economic development; however, many still face challenges related to business management, marketing, human resource management, and financial administration. This community service program aimed to improve the managerial capacity of Salon Mitra SME in Selong, East Lombok through counseling, training, and mentoring activities. A participatory approach was employed, consisting of problem identification, counseling, training, mentoring, and evaluation stages. The materials delivered covered production management, human resource management, marketing strategies, financial management, and entrepreneurship. The results indicated an improvement in participants’ understanding of business planning, human resource management, social media-based marketing, simple financial record keeping, and entrepreneurial mindset development. The program also encouraged greater awareness of service innovation and more professional business management practices. Although quantitative measurements of business performance improvement were not conducted, the program contributed positively to strengthening managerial capacity and enhancing the competitiveness of the partner enterprise.